Coronavirus disease-19 quarantine is more detrimental than traditional off-season on physical conditioning of professional soccer players - Grazioli, R.; Loturco, I.; Baroni, B. M.; Oliveira, G. S.; Saciura, V.; Vanoni, E.; Dias, R.; Veeck, F.; Pinto, R. S.; Cadore, E. L. (The Journal of Strength and Conditioning Research, 2020)
Beyond the severe health crisis, the coronavirus disease 2019 has also affected the high-performance sports scenario. In soccer, practitioners are concerned about the effects of long-term detraining on players' conditioning, and caution is required when activities return. This study assessed body composition, jump and sprint performance, hamstring eccentric strength, and intermittent cardiorespiratory fitness of 23 male professional soccer players who returned to training activities after 63 days of quarantine. The results were compared with their physical condition assessed before a pre-season phase as soon as they returned to training after a regular 24-day off-season period. In comparison with after off-season assessments, the quarantine induced significant increases in body mass, body fat mass, 10- and 20-m sprint times as well as decreases in countermovement jump height (p < 0.05). There were no significant changes in hamstring eccentric strength, squat jump height, and cardiorespiratory fitness (p > 0.05). In summary, we showed that 63 days of quarantine impaired several physical performance measures compared with regular off-season in soccer players. Given the present results, special attention should be given to body composition-related and speed power-related capabilities after long-term detraining in professional soccer.